Anteseden Model Kinerja Tenaga Kependidikan Universitas Jambi : Analisis Structural Equation Modelling - Aprillitzavivayarti Aprillitzavivayarti; Robin Pratama (Universitas Pendidikan Mandalika, 2023)
This study examines the direct effect of entrepreneurial orientation, knowledge management, innovation capacity, and strategy implementation on the performance of Jambi University teaching staff. This research used a survey method with a quantitative approach. The research sample was 197 Education Staff at the University of Jambi. The research instrument used a questionnaire and was analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM). The results of this study indicated that; (1) entrepreneurial orientation and knowledge management had a significant and positive impact on increasing innovation capacity. That is, the higher the entrepreneurial orientation and knowledge management by institutions, in this case at the University of Jambi, the better the innovation in business competitiveness. (2) knowledge management did not affect strategy implementation. It means that knowledge management indirectly has no role in the performance and implementation of strategies at Jambi University in the context of business competitiveness in the BLU financial management pattern. (3) entrepreneurial orientation, innovation capacity, and strategy implementation had a significant effect on improving the performance of Jambi University institutions, meaning that the higher the entrepreneurial orientation, innovation capacity, and strategy implementation, the better the performance of Jambi University institutions in supporting universities with public service agency status (BLU).